Analisis Kemandirian Keuangan Daerah pada Kabupaten dan Kota di Pulau Jawa Tahun 2016 – 2023 - Harahap, Muhammad Nasim; Yaqien , Muhammad Giri Ainul; Sutjipto , Hady; Desmawan , Deris (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2024)
This research was conducted with the aim of determining whether or not there is an influence of the Human Development Index, Capital Expenditure, Employee Expenditure and Population Density factors on Regional Financial Independence in Regencies and Cities on the Island of Java in 2016-2023. This research consists of 93 regencies/cities on the island of Java. The data used in this research uses secondary data from panel data for 8 (eight) years 2016-2023. Data obtained from the Directorate General of Fiscal Balance and the Central Statistics Agency were processed using the Eviews 10 application. The results of this research partially show that the Human Development Index variable has a significant effect on Regional Financial Independence, the Capital Expenditure variable has no effect on Regional Financial Independence, the Employee Expenditure variable has an effect significant effect on Regional Financial Independence, and Population Density has a significant effect on Regional Financial Independence. Simultaneous results of the variables Human Development Index, Capital Expenditures, Employee Expenditures, and Population Density have a significant effect on the Financial Independence of Regencies and Cities on the Island of Java in 2016-2023. The results of the coefficient of determination test produce that the independent variable influences the dependent variable by 92.76% and the remaining 7.24% is explained by other variables not included in the regression and panel estimation models in this study.